Analysis of parameters affecting thrust and base pressure in suddenly expanded flow from nozzle - Pathan, Khizar Ahmed; Syed, Ashfaq; Dabeer, Prakash S; Khan, Sher Afghan (Penerbit Akademia Baru, 2019)
In the case of flow from the nozzle, the net thrust is the vital and critical consideration. The net thrust force is the difference of the thrust developed by the jet from the nozzle and the base drag. The pressure in the base area of a duct with the sudden expansion usually is lower than the ambient atmospheric pressure, which is responsible for creating a very high value of the base drag. It is essential to design an enlarged duct and selection of the suitable values of the flow parameters for efficient utilization of the fuel by producing the high thrust and low base drag. In this research paper, various combinations of parameters are analyzed using CFD analysis and by considering the Design of Experiments & ANOVA. The parameters considered for this research work are Nozzle Pressure Ratio (NPR), Length to Diameter Ratio (L/D), Mach number (M), Inlet temperature of air (T), and the Area Ratio (AR). Based on the results obtained during the present study, it is found that the base pressure and thrust created by the flow are dependent and functions of the following parameters, and they are the NPR, the Mach number, the area ratio of the duct (AR), and the L/D. The inlet temperature of the air does not have any significant effect on the base pressure as well as on the Thrust.